Case Report: A rare instance of acute appendicitis induced by Balantidium Coli parasitic infection - Alzate-Ricaurte, Sergio; Garcia Moreno, Isabel Cristina; Serna Lorza, Juan David; Hincapie-Ayala, Daniela; Diaz, Maria Camila; Alzate Gallego, Edgar Darío; Sanchez Sanchez, Juan Pablo (Frontiers in Pediatrics, 2024)
Introduction: Acute appendicitis secondary to parasitic infections is uncommon, being detected in less than 1% of cases. Balantidium coli is a parasite found in pigs and primates with zoonotic potential. To date, only three cases of acute appendicitis induced by this parasite have been documented globally.Case: A 7-year-old female patient, who consumed pork daily, presented to the emergency department with a one-day history of abdominal pain in the lower quadrants, described as colic-like, alongside abdominal distension. Initial abdominal radiography led to a diagnosis of intestinal obstruction. Conservative management without therapeutic response necessitated referral to a higher complexity center. Upon admission, an abdominal computed tomography scan diagnosed acute appendicitis and secondary ileus. During surgical intervention, an appendiceal phlegmon formed by loops of the small intestine was mechanically released, revealing a perforated appendix with extensive fecal peritoneal contamination. Pathological analysis identified an inflammatory infiltrate and the presence of Balantidium coli trophozoites. Medical treatment included Piperacillin-Tazobactam and Metronidazole. The patient was discharged after 10 days of medical treatment.Discussion: Acute appendicitis caused by Balantidium coli is a rare occurrence. It is crucial to identify parasites in pathological samples due to their impact on postoperative management. The close contact between humans and pigs, especially in developing countries, suggests that the prevalence of parasitic infection and colonization by Balantidium coli may be higher than currently recognized. Regarding the identification of this patient's specific exposure, the regular consumption of pork suggests the hypothesis that improper processing is linked to the acquisition of the parasitic infection.